Epigenetic Modifications and Therapy in Chronic Obstructive Pulmonary Disease (COPD): An Update Review - Lingzhi Zhang; Hamed Valizadeh; Iraj Alipourfard; Ramtin Bidares; Leili Aghebati‐Maleki; Majid Ahmadi (2020)
Chronic obstructive pulmonary disease (COPD) that is one of the most prevalent chronic adult diseases and the third leading cause of fatality until 2020. Elastase/anti-elastase hypothesis, chronic inflammation, apoptosis, oxidant-antioxidant balance and infective repair cause pathogenesis of COPD are among the factors at play. Epigenetic changes are post-translational modifications in histone proteins and DNA such as methylation and acetylation as well as dysregulation of miRNAs expression. In this update review, we have examined recent studies on the upregulation or downregulation of methylation in different genes associated with COPD. Dysregulation of HDAC activity which is caused by some factors and miRNAs plays a key role in the suppression and reduction of COPD development. Also, some therapeutic approaches are proposed against COPD by targeting HDAC2 and miRNAs, which have therapeutic effects.